2008
DOI: 10.1177/147323000803600526
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Inflammation in Atrial Fibrillation following Open Heart Surgery

Abstract: This study investigated the role of systemic inflammation in the development of atrial fibrillation (AF) after coronary artery bypass grafting (CABG). CABG was performed using cardiopulmonary bypass in 77 patients. Pre-operative AF was present in six patients (7.8%) and postoperative AF developed in 13 (18.3%) of the 71 patients with pre-operative sinus rhythm. Post-operative mediastinal drainage was significantly increased in patients with post-operative AF compared with those with sinus rhythm. Plasma E-sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 23 publications
0
29
0
2
Order By: Relevance
“…Inflammation and oxidative stress may play a key role in the establishment of an appropriate substrate for the arrhythmia [8,26,27] rendering the patients susceptible to the inflammatory injury associated with cardiopulmonary bypass [28,29]. Previous reports have described that increased levels of pro inflammatory cytokines [27,30], white blood cell count [31][32][33] and complement-CRP complexes [34] may predict POAF development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Inflammation and oxidative stress may play a key role in the establishment of an appropriate substrate for the arrhythmia [8,26,27] rendering the patients susceptible to the inflammatory injury associated with cardiopulmonary bypass [28,29]. Previous reports have described that increased levels of pro inflammatory cytokines [27,30], white blood cell count [31][32][33] and complement-CRP complexes [34] may predict POAF development.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been extensively investigated, the precise etiology of POAF remains elusive [8]. Inflammation and oxidative stress may play a key role in the establishment of an appropriate substrate for the arrhythmia [8,26,27] rendering the patients susceptible to the inflammatory injury associated with cardiopulmonary bypass [28,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the normal ageing process, cardiac surgery itself induces a systemic inflammatory response [17] . A previous study reported higher serum resistin levels both in the pre-and postoperative phases along with other proinflammatory markers (IL-6, IL-10, and CRP) [18] . These studies support the finding that inflammatory pathways, from either the advancing age or surgery or even both, could be a potential reason for the development of postoperative AF.…”
Section: Discussionmentioning
confidence: 99%
“…4 Another approach is the use of leukocyte filters, 5 as there seems to be a connection between atrial fibrillation and inflammation. 6,7 Indeed, systemic inflammation can elicit atrial fibrillation by activating the complement system and stimulating release of activated cytokines.…”
Section: Introductionmentioning
confidence: 99%